Graph-based analysis of Armenia's connectivity in the EU-Asia trade network: Strategic role and limitations - Vardan Atoyan; Diana Matevosyan (OrdnungsPolitisches Portal (OPO), 2025)
The growing geopolitical tensions and regional instabilities in Eurasia raise urgent questions about the resilience of trade routes and infrastructure connectivity. This paper applies a graphbased approach to model the EU-Asia trade network and explores Armenia's potential as a transit hub within the framework of the Global Gateway strategy. The authors construct a weighted network of major regional players based on bilateral trade volumes, geographic distances, and route accessibility. In this network, nodes represent key countries, while edges capture trade relationships, with weights reflecting trade intensity and logistical characteristics. Using a set of graph-theoretical metrics, including degree centrality, betweenness centrality, closeness centrality, and eigenvector centrality, the authors assess the country's importance within the network, identifying its position as a potential chokepoint or facilitator of alternative trade routes. Stress-testing scenarios, including border closures, sanctions, or the reopening of previously closed borders, are simulated to evaluate the impact on trade flows and regional logistics. These scenarios simulate the dynamic nature of trade flows, considering disruptions that could reshape existing networks. Results indicate significant shifts in the network structure under stress, highlighting opportunities for Armenia to strengthen its strategic position as an alternative node in critical corridors.
Keywords: 330; Graph; Logistic Network; Eurasian Corridors; Trade; Armenia